2021
DOI: 10.3389/fpsyt.2021.630162
|View full text |Cite
|
Sign up to set email alerts
|

The Complex Interaction Between the Major Sleep Symptoms, the Severity of Obstructive Sleep Apnea, and Sleep Quality

Abstract: Introduction: Little information exists in the general population whether clinical presentation phenotypes of obstructive sleep apnea (OSA) differ in terms of sleep quality and comorbidities.Aim: The purpose of our study was to assess possible differences between symptomatic and asymptomatic OSA patients concerning syndrome's severity, patients' sleep quality, and comorbidities.Subjects and methods: First, in a nationwide, stratified, epidemiological survey, 4,118 Cypriot adult participants were interviewed ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 59 publications
0
13
0
1
Order By: Relevance
“…However, no influence of ESS or AIS score on CVD was noted in our population, questioning if the ESS or AIS tools are sufficient, when employed alone, to characterize the excessive sleepiness or insomnia phenotype of OSA patients at increased risk for cardiovascular events. Furthermore, it also remains unclear if sleepiness or insomnia symptoms are associated with an increase of prevalence in CVD in OSA patients [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…However, no influence of ESS or AIS score on CVD was noted in our population, questioning if the ESS or AIS tools are sufficient, when employed alone, to characterize the excessive sleepiness or insomnia phenotype of OSA patients at increased risk for cardiovascular events. Furthermore, it also remains unclear if sleepiness or insomnia symptoms are associated with an increase of prevalence in CVD in OSA patients [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Of 269 patients newly diagnosed with OSA (aged 21–70 years; 73% men), 54% were categorized as having insomnia [ 27 ]. In another series of 155 OSA patients, 49% had an Athens Insomnia Scale score of at least 6 [ 28 ]. In a series of 296 OSA patients, 80% reported at least one major symptom of insomnia: 57% reported sleep onset insomnia, 68% sleep maintenance insomnia and 48% had early morning awakenings.…”
Section: Comorbid Insomniamentioning
confidence: 99%
“…Some researchers suggest OSA patients do not only suffer from depressive symptoms caused by OSA but they have mood components as well [60]. A pilot study published in 2020 found that there is no association between OSA and depression severity.…”
Section: Osa and Depressive Disordermentioning
confidence: 99%